HIPC debt relief and policy reform incentives - Jean-Claude Berthélemy (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2001)
In this paper, I discuss the incentives that the HIPC Initiative could create in debtor countries in favour of economic adjustment and reform. The usual debt-overhang argument, stating that debt relief will increase the net benefits of reforms, needs to be revisited in this context. First, the HIPC Initiative does not provide pure debt relief, but also creates new public spending obligations on poverty reduction programmes. Second, not all HIPCs can be considered as enjoying good economic governance, while the debt-overhang argument assumes a welfare-maximizing government. I show that standard positive incentives can be obtained only in good economic governance instances. I suggest that, in other instances, the outcome of HIPC programmes could be improved if external shocks were taken into account in their design.
Keywords: F34; 330; debt overhang; incentives; social expenditure; investment; Schuldenerlass; Entwicklungsländer